The results of palynogical studies of the Holocene deposites in the highlands of the Lagodekhi Reservation (Eastern Georgia). - Kvavadze, Eliso V; Efremov, Yurii Y (PANGAEA, 1990)
Limno-glacial deposits 110 cm in thickness in the upper alpine belt have been investigated. It is established that during the Yuanakhchiri period of glaciation in the region under study a glacial cirque was situated at an altitude of 2750 m a.s.l. After the glacier retreated, a lake was formed in its bed which existed till the second noticeable cooling in the second half of SA2 (1600-1500 years ago).
Pollen profile LAGODEH, Lagodekhi, Georgia
Keywords: Abies nordmanniana; Acer; Alnus; Artemisia; Aster; Betula; Boraginaceae; Botrychium lunaria; Campanula; Carpinus betulus; Carpinus orientalis; Caryophyllaceae; Castanea sativa; Cerealia-type; Chenopodiaceae; Cichorium; Cirsium; Compositae; Corylus; Cyperaceae; DEPTH, sediment/rock; Ephedra; Fagus orientalis; Geraniaceae; Gramineae; Indeterminable: unknown; Juglans regia; Juncus; Knautia; Labiatae; LAGODEH; Lagodekhi, Georgia; Leguminosae; Liliaceae; Onagraceae; Picea orientalis; Pinus; Plantaginaceae; Plumbaginaceae; Polygonaceae; Polypodiaceae undifferentiated; Polypodium vulgare; Pterocarya pterocarpa; Quercus; Ranunculaceae; Rhododendron; Scabiosa; Spade; SPADE; Sparganium; Sphagnum; Taraxacum; Tilia; Ulmus; Umbelliferae; Valeriana; Veronica; Viola